2021
DOI: 10.1016/j.devcel.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Tissue mechanics in stem cell fate, development, and cancer

Abstract: Cells in tissues experience a plethora of forces that regulate their fate and modulate development and homeostasis. Cells sense mechanical cues through localized mechanoreceptors or by influencing cytoskeletal or plasma membrane organization. Cells translate force and modulate their behavior through a process termed mechanotransduction. Cells tune their tension upon exposure to chronic force by engaging cellular machinery that modulates actin tension, which in turn stimulates matrix remodeling and stiffening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 151 publications
(145 reference statements)
0
62
0
Order By: Relevance
“…Besides cytokine/ECM signaling, other feedback amplifications in ROS responses include the mitochondria-dependent, ROS-induced ROS release, and the mitochondria-mediated crosstalk between ROS and the calcium flux, a detailed review of which can be found elsewhere ( Zorov et al, 2014 ; Gorlach et al, 2015 ; Javadov, 2015 ; Feno et al, 2019 ). Herein, we focus on the coupling of NOX with cell mechanics and mechanotransduction, an emerging issue in the fields of stem cell research, cell therapy, wound healing, and cancer ( Paszek et al, 2005 ; Kono et al, 2012 ; Liu et al, 2020a ; Wilkinson and Hardman, 2020 ; Bergert et al, 2021 ; Hayward et al, 2021 ). In fact, a great deal of interest has recently been raised in the roles of cell mechanics in the key cellular processes, such as proliferation, cell death, cell differentiation, and cell migration ( Chen et al, 1997 ; Horowitz et al, 1999 ; Lecuit and Lenne, 2007 ; Settleman and Baum, 2008 ; Grosberg et al, 2011 ), and the maintenance of stem cell pluripotency ( Discher et al, 2009 ; Jaalouk and Lammerding, 2009 ; Mammoto and Ingber, 2009 ; Wozniak and Chen, 2009 ).…”
Section: Main Textmentioning
confidence: 99%
“…Besides cytokine/ECM signaling, other feedback amplifications in ROS responses include the mitochondria-dependent, ROS-induced ROS release, and the mitochondria-mediated crosstalk between ROS and the calcium flux, a detailed review of which can be found elsewhere ( Zorov et al, 2014 ; Gorlach et al, 2015 ; Javadov, 2015 ; Feno et al, 2019 ). Herein, we focus on the coupling of NOX with cell mechanics and mechanotransduction, an emerging issue in the fields of stem cell research, cell therapy, wound healing, and cancer ( Paszek et al, 2005 ; Kono et al, 2012 ; Liu et al, 2020a ; Wilkinson and Hardman, 2020 ; Bergert et al, 2021 ; Hayward et al, 2021 ). In fact, a great deal of interest has recently been raised in the roles of cell mechanics in the key cellular processes, such as proliferation, cell death, cell differentiation, and cell migration ( Chen et al, 1997 ; Horowitz et al, 1999 ; Lecuit and Lenne, 2007 ; Settleman and Baum, 2008 ; Grosberg et al, 2011 ), and the maintenance of stem cell pluripotency ( Discher et al, 2009 ; Jaalouk and Lammerding, 2009 ; Mammoto and Ingber, 2009 ; Wozniak and Chen, 2009 ).…”
Section: Main Textmentioning
confidence: 99%
“…The extracellular matrix (ECM) influences tissue development and homeostasis 9,11 . ECM properties also regulate the stem cell niche and its stiffness modulates stem cell growth, survival and tissue-specific differentiation [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…A stiff ECM modifies cell and tissue behavior, in part, by regulating the context of cellular signaling to influence gene expression 9,11,23 . Specifically, a stiff ECM fosters the assembly of integrin focal adhesions which potentiate growth factor dependent ERK and phosphatidylinositol 3-kinase (PI3K) signaling [24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Direct transduction of mechanical tension from the ECM to the cellular actin cytoskeleton can also lead to activation of mechanosensitive ion channels, which themselves mediate chemical signaling by regulating ion flux [9]. The vast majority of cellular functions can therefore be influenced by mechanical signals transduced via the ECM, both in development [10] as well as health and disease [11]. These mechanisms are nevertheless reciprocal, as mechanosensation and transduction can in turn induce the production and remodeling of the ECM, thereby modifying its mechanical properties [12,13].…”
Section: Introductionmentioning
confidence: 99%